(untitled) (Scientific journal of the Fergana State University, 2024)
The component composition of the essential oil obtained by hydrodistillation from the aerial part of the plant Salvia deserta (desert sage), growing in the vicinity of the village of Chodak in the Namangan region, was studied. In the composition of the essential oil, 86 components were identified by GC-MS, which is 92.7% of the total mass of the oil. It has been established that the composition of the essential oil is dominated by sesquiterpene hydrocarbons (32.2%) and oxidized monoterpenes (17.9%). The major components of the essential oil are β-caryophyllene (12.8%), germacrene D (9.9%), spathulenol (8.5%), caryophyllene oxide (6.8%), camphor (5.7%), terpinen-4-ol (5.7%), dihydroselarene (3.3%), 1,8-cineole (3.1%).